ASPEK-ASPEK EPISTEMOLOGI DALAM MANAJEMEN PENDIDIKAN ISLAM - Adawiah, Diah Robiatul; Ambarawati, Puji; Marfuah, Pupu; Hidayat, Wahyu; Fauzi, Anis (Jurnal Manajemen Pendidikan Islam Darussalam, 2024)
The purpose of this study is to determine the source of knowledge, and the role and diffusion of epistemology in the management review of Islamic Education. The method that researchers use is library research in the form of references from various library data sources that are ready to use so that they can be used immediately and are not limited by space and time. The results of the study show that aspects of epistemology are related to the way understanding and knowledge are obtained in the context of Islamic education. It includes teaching methods, sources of knowledge, and the process of understanding Islamic concepts. The role of epistemology in the management of Islamic education ensures that the methods and knowledge conveyed are in accordance with Islamic scientific principles. By understanding and applying this aspect of epistemology in the management of Islamic education, it is hoped that educational institutions can make a positive contribution in forming individuals who are knowledgeable, moral, and able to make a positive contribution to society and Muslims as a whole.